INTERAKSI EKSTRAK DAUN TEH HIJAU DAN BUAH CABE MERAH SEBAGAI ANTIHIPERGLIKEMIA ANAK - Ikhda Nur Hamidah Safitri, Cikra; Anjar Wati, Dewi (Jurnal Insan Farmasi Indonesia, 2025)
Diabetes mellitus is a condition in which blood sugar levels are very high and cannot be controlled for an extended period. Therefore, more effective alternative treatments are needed. One of the materials being studied is green tea leaves (Camellia sinensis L) and red chili peppers (Capsicum annuum L), both of which are known to have antihyperglycemic effects. This study aims to determine the interaction between green tea leaf extract and red chili pepper extract in reducing blood glucose levels in mice with elevated blood sugar. A total of 25 mice were used and divided into 5 groups, each containing 5 mice. In the treatment, groups were given green tea leaf extract at a dose of 37.5 mg per 30 grams of body weight per day, red chili pepper extract at 12.5 mg per 30 grams of body weight per day, and metformin as a comparison at a dose of 169 mg per gram for 1 to 6 days or until blood glucose levels decreased. The parameter observed was the decrease in blood glucose levels. The results showed that the administration of green tea leaf extract and red chili pepper extract could significantly reduce blood glucose levels in mice.